2021
DOI: 10.3892/br.2021.1475
|View full text |Cite
|
Sign up to set email alerts
|

Screening of anti‑chronic nonbacterial prostatitis activity of different extractions of the aerial part of Glycyrrhiza uralensis, and network pharmacology research

Abstract: In the present study, anti-chronic nonbacterial prostatitis (CNP) pharmacological experiments using water and ethanol extraction of the aerial parts of Glycyrrhiza uralensis were performed to select the best active parts by comparing their efficacy in a CNP model established by injecting carrageenin into the ventral lobe of rat prostate. The anti-CNP activities and expression of serum inflammatory factors in rats were also analyzed. A Protein-Protein Interaction network was constructed, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…The aerial part of G. uralensis has been studied in our research group for many years, but it has not been used in clinical practice. In our previous study [ 1 ], 1 g/kg of the aerial part of G. uralensis extract was determined to be the best effective dose to induce anti-CNP activity. According to the conversion ratio between human and rat, the dosage of human should be 0.159 g/kg.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The aerial part of G. uralensis has been studied in our research group for many years, but it has not been used in clinical practice. In our previous study [ 1 ], 1 g/kg of the aerial part of G. uralensis extract was determined to be the best effective dose to induce anti-CNP activity. According to the conversion ratio between human and rat, the dosage of human should be 0.159 g/kg.…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of total flavonoids in the dry stem and leaves of Glycyrrhiza uralensis Fisch. (licorice, G. uralensis ) is up to 5.64% [ 1 ]. We have reported previously that the aerial parts of G. uralensis exhibit antioxidant [ 2 ], antibacterial [ 3 ], anti-inflammatory [ 2 ], antitumor [ 4 ] and antidiabetic [ 5 ] properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nine herbal medicines have been reported to have various biological effects, for example, anti-inflammatory, antioxidant, anticancer, antitumor, antidiabetes, antiaging, anti-obesity, neuroprotective, and antibacterial activities [6][7][8][9][10][11][12][13][14]. Recently, a study on the safety of a single administration of GHT was reported by An et al [4], but few studies on the biological activity have been reported.…”
Section: Introductionmentioning
confidence: 99%